The Coal Pillar Width Effect of Principal Stress Deflection and Plastic Zone Form of Surrounding Rock Roadway in Deep Excavation. (18th March 2022) - Li, Ji; Zhang, Rongguang; Qiang, Xubo
Abstract : In order to explore the influence of coal pillar width on the principal stress deflection and plastic zone form of surrounding rock in deep roadway excavation, taking 11030 working face transportation roadway of Zhaogu No. 2 Coal Mine as engineering background, theoretical analysis, numerical simulation, and field detection were used to study the effect of coal pillar width on principal stress deflection and plastic zone form and field detection and verification of plastic zone form of surrounding rock in 11030 transportation roadway. The results show that the maximum principal stress is deflected in the vertical direction, which in roadway surrounding rock excavation. The coal pillar width effect of principal stress deflection on both sides of roadway roof and floor and inside coal pillar are more obvious than that of middle roof and floor, coal pillar edge and coal wall position. The deflection of the principal stress affects the morphological distribution of the plastic zone of the surrounding rock, which led to the width effect of coal pillar in roof, and two sides plastic zone are more obvious than that in floor. The principal stress deflection of roadway surrounding rock is highly consistent with the maximum damage depth of plastic zone, and at the same time, the drilling peep results of surrounding rock are basically consistent with the form characteristics of plastic zone in numerical simulation. On this basis, the surrounding rock reinforcement support scheme of 11030 working face transportation roadway was proposed.